Ventral slot in the clinical recovery of dogs with lateralized compression as a result of cervical intervertebral disc disease - 20 cases (2008-2018) - Schwab,Marcelo Luís (2020)
ABSTRACT: The objective of this study was to verify the clinical recovery of dogs that underwent ventral slot surgical decompression with lateralized compressions of the cervical spinal cord caused by intervertebral disc disease (IVDD). Twenty patients were selected in different degrees of neurological dysfunction with definitive diagnosis of lateralized compression by cervical IVDD. Postoperative clinical recovery was assessed in patients who had undergone at least two months of the surgical procedure. There was a satisfactory recovery in 19 dogs (95%) and unsatisfactory recovery in another (5%), showing a significant clinical improvement (p<0.05) in the use of this technique in lateralized compression cases. The ventral slot promotes satisfactory clinical recovery of dogs with lateralized compression of the spinal cord caused by cervical IVDD and may be indicated as a surgical alternative.